Formulation of Timolol Maleate Sustained-release Matrix Tablets - Satya, B. Lakshmi (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Pharmaceutical products designed for oral delivery are mainly conventional drug delivery systems, which are designed for immediate release of drug for rapid/immediate absorption. A controlled drug delivery system is usually designed to deliver the drug at particular rate. Safe and effective blood levels are maintained for a period as long as the system continues to deliver the drug. This predetermined rate of drug release is based on the desired therapeutic concentration and the drugs pharmacokinetics. An controlled release formulation of Timolol maleate to maintain constant therapeutic levels of the drug for over 10 h. Timolol maleate-controlled release matrix tablets are prepared by wet granulation method with different grades of HPMC. An efficient extended release formulation of Timolol maleate could be designed as controlled release tablets. Combination of HPMC K100M and HPMC K15M was extended the release for 10 h. No significant change in the drug release was observed with changing the ratio of polymers. All the batches (F26 to F30) have shown burst release also. The release process involves anomalous diffusion mechanism or diffusion coupled with erosion.